The incidence of unexpected delays in uploading outside radiologic images in the transfer of patients with major trauma - Si Jun Woo; Yong Oh Kim; Hyung Il Kim (Journal of Trauma and Injury)
Purpose Critically ill patients are frequently transferred from one point of care to a hospital that can provide a higher level of care. To achieve optimal treatment within the targeted window of time necessary for time-sensitive cases like major trauma, rapid transportation and decision making are essential. Transferred patients have often undergone radiologic imaging at the referring hospital. Examining these outside images is paramount. Therefore, this study was conducted to estimate the upload time of outside images. Methods This retrospective study was conducted from January to April 2020. Patients transferred from other hospitals with digitally recorded CDs or DVDs of radiologic or diagnostic images were included. When the patients were registered at the emergency department reception desk, the digital images were transmitted to our picture archiving and communication system using transmission software. The time of upload and the numbers of digital images were recorded. The time interval from patient registration to the time of upload was calculated. Results The median number of images was 688 in the trauma team activation (TTA) group (688 in the TTA group, 281 in the non-TTA trauma group, and 176 in the nontrauma group, respectively; P<0.001). The median upload time was 10 minutes. The longest upload time was 169 minutes. The upload time was more than 20 minutes in 12 cases (19.4%). Conclusions Patients with major trauma bring more images than patients with other diseases. Unexpected delays (>20 minutes) were noted in approximately 20% of cases. It is necessary to minimize this time.